Relaciones Que Se Tejen Entorno A Las Actividades Ocupacionales De Los Niños Down De La Casa De La Cultura Del Municipio De Montenegro (2014)
The present investigation includes the relationships that weave around the occupational activities of the children down to the house of culture of the municipality of Montenegro. It is characterized by a micro ethnography with a study of qualitative methodology, using the history of life and the in-depth interviews as a technique for data collection. It is concluded that the activities occupational allow weave different relations drive, sports, artistic, playful, Labor Day and that in turn will weave links and affective relationships, it is therefore considered necessary to strengthen and develop this type of relationship.